Theoretical determination of level delocalizations, plasma shifts and radiative properties of fusion relevant Ni XXII in finite temperature dense plasmas using a generalized analytical b-potential. (May 2021) - Chen, Z.B.; Tian, Y.S.; Yin, Y.M.; Qi, Y.Y.; Zhao, G.P.; Shen, X.Z.; Wang, K.
Highlights: We proposed a model to calculate the level delocalizations, plasma shifts and radiative properties of ions in finite temperature dense plasmas. The generalized analytical b-potential combined with the multi-configuration Dirac-Fock approximation. is adopted. The present work is of great interest for the high-energy density physics community. Abstract: We propose a novel relativistic method to explore the atomic structure of highly charged ions perturbed by a dense plasma. The calculations are performed within the general framework of the ion sphere theory and application of the generalized analytical b -potential combined with the multi-configuration Dirac-Fock approximation. In the method, the relativistic effects provided by the Dirac-Coulomb Hamiltonian, Breit interaction and two kinds of quantum electrodynamics corrections, self-energy and vacuum polarization, are accounted for systematically via perturbation theory. The level delocalizations, line shifts and radiative properties among the levels of the 2 s x 2 p y ( x + y =5) configurations of Ni XXII under the finite temperature dense plasma conditions are demonstrated for illustrative purposes. Such ions can exist in inertial confinement devices or in laser-produced plasmas. Systematic changes are determined for the properties under study in respect of increased temperature and electron density. The obtained atomic structure, line shift, and level delocalization are essential fundamental properties for advanced diagnostics, equation of state calculations, line identifications, and benchmark data for ionization balance calculations ect.